Pengaruh Status Gizi Terhadap Kejadian Anemia Pada Ibu Hamil - Katili, Dwi Nur Octaviani; Sondakh, Levana; Katili, Tressan Eka Putri S.; Adam, Jusri; Hiola, Fidyawati Aprianti A. (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
Anemia is a condition in which the hemoglobin level in the blood is below normal. During pregnancy, the need for iron and other nutrients increases significantly to support fetal growth and physiological changes in the mother. Therefore, pregnant women are very susceptible to anemia if nutritional intake is insufficient or there is impaired nutrient absorption. The prevalence of anemia in pregnant women is quite high in various regions, and this condition can have serious impacts on the health of the mother and fetus. Anemia can increase the risk of pregnancy complications such as premature birth, low birth weight, and maternal and neonatal death. In addition, anemia can also cause fatigue, decreased immunity, and impaired cognitive development in children after birth. To determine the relationship between nutritional status (BMI and LILA) and anemia in pregnant women. Quantitative research design with analytical survey with a cross-sectional approach, a population of 34 people with a sample of 34 people or total sampling. The results of the study showed that most BMI was in the abnormal category of 25 people with a P value of 0.033 <0.05 and LILA was in the category of £ 23.5 cm of 28 people with a P value of 0.021 <0.05. There is a relationship between nutritional status of BMI and LILA with anemia in pregnant women in the working area of the Gorontalo Regency Health Center.